2003
DOI: 10.1038/sj.gt.3301889
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline-regulated lentiviral vector system with a novel reverse transactivator rtTA2S-M2 shows a tight control of gene expression in vitro and in vivo

Abstract: Regulated expression of therapeutic genes is required for long-term gene therapy applications for many disorders. Here we describe a doxycycline (dox)-regulated lentiviral vector system consisting of two HIV-1-based self-inactivating viruses. One of the vectors is constitutively expressing a novel improved version of the tetracycline reverse transactivator rtTA2 S -M2 and the other has a rtTA responsive promoter driving the expression of b-galactosidase gene (lacZ). The rtTA2 S -M2 has highly improved properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 34 publications
(18 reference statements)
2
58
2
1
Order By: Relevance
“…Recently, it has been demonstrated that amino acid substitutions in rtTA have greatly improved the transcriptional activity and Dox-sensitivity of the protein (Zhou et al, 2007). In addition, modifications in the TRE-CMV promoter have been continued to further reduce the background activity of the Tet-on system (Koponen et al, 2003). Thus, a combination of our zebrafish line with an effective TRE-CMV promoter is required for functional analysis of certain genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that amino acid substitutions in rtTA have greatly improved the transcriptional activity and Dox-sensitivity of the protein (Zhou et al, 2007). In addition, modifications in the TRE-CMV promoter have been continued to further reduce the background activity of the Tet-on system (Koponen et al, 2003). Thus, a combination of our zebrafish line with an effective TRE-CMV promoter is required for functional analysis of certain genes.…”
Section: Discussionmentioning
confidence: 99%
“…While a dose-response relationship exists in chemotherapy, it may be possible that this relationship reaches a plateau at a higher dose due to limitations of normal organ toxicity. The Tet-On system, which uses an E. coli gene regulatory system, 11 appears to fulfill the criteria for clinical application with several advantages: 6,7,11,26 (1) gene expression is easily regulated by administration of Dox; (2) Dox is minimally toxic and has been widely used as an antibiotic; and (3) Dox acts specifically on the target gene and does not activate other Results in this report suggest that the HSVtk/Tet-On/ GCV system is a feasible method in the treatment of breast cancer and other solid tumors. Our data show that there is an apparent dose-dependent relationship between HSVtk gene expression and Dox concentration in infected MCF-7 cells when the concentration of GCV is at 1 mg/ ml.…”
Section: Discussionmentioning
confidence: 99%
“…This result requires the therapeutic gene expression to be regulated tightly in administration, induction, and termination. 7 To achieve this set of conditions, several inducible eukaryotic gene promoters have been used to deliver genes in a regulated manner. The promoter inducers include steroid hormones, oxygen, heavy metals, and physical stimulus (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although the binary strategy imposes the necessity that each target cell will have to be efficiently transduced by two vectors, it seems, however, to be less leaky by comparison with the single-based system, which therefore is better suited to the desired induction parameters. A more advanced tetracycline regulation design has recently been applied in the LV field context where the use of a codon-optimized tetracycline transactivator has been shown to significantly reduce the leakiness in different cell types [138,141].…”
Section: Transcriptional Regulationmentioning
confidence: 99%